Keterampilan Bahasa Indonesia untuk Kesuksesan Karir di Era Digital (Indo-MathEdu Intellectuals Journal, 2024)
Indonesian has an important role when it comes to communication. Along with the times through digital transformation that language often transforms following trends that occur so that it has an impact on human requirements to improve language skills, to produce effective communication. This article aims to know the importance of Indonesian language skills to achieve career success in the digital era. Through a qualitative approach using descriptive qualitative methods. The research subjects were selected using purposive sampling techniques, namely the determination of subjects using certain criteria. Data collection is done through interviews. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that Indonesian language skills are an important element in career success in the digital era. During advances in information and communication technology, Indonesian language proficiency is not only needed in professional contexts, but also in daily interactions. This research shows that mastering Indonesian well provides significant competitive advantages, such as increasing career opportunities, building strong relationships, and expanding the range of jobs